2014
DOI: 10.1109/tap.2013.2295595
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Depth of Microwave Radiation for Internal Body Temperature Measurement

Abstract: This paper investigates modeling of the interaction of human tissues with a probe antenna situated on the surface of the skin. The goal is to differentiate temperature changes at different depths under the skin for passive radiometric measurements of internal body temperature. An improved metric is defined in order to differentiate thermal power radiated from a specific part of the tissue relative to the total thermal power received by the probe antenna. The frequency range between 0.5 and 3 GHz is investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The exact sensing depth strongly affects the accuracy of the soil moisture and soil temperature profile retrieval, as the soil moisture and soil temperature near the land surface has strong gradients and can be varying dramatically. One way to infer soil moisture sensing depth is by correlating brightness temperature and in-site soil moisture time-series so that the soil moisture layer that corresponds best with brightness temperature is considered to be the sensing layer [24,25]. To get soil moisture at different depth, this method always requires precise and vertically dense soil profile measurement or simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The exact sensing depth strongly affects the accuracy of the soil moisture and soil temperature profile retrieval, as the soil moisture and soil temperature near the land surface has strong gradients and can be varying dramatically. One way to infer soil moisture sensing depth is by correlating brightness temperature and in-site soil moisture time-series so that the soil moisture layer that corresponds best with brightness temperature is considered to be the sensing layer [24,25]. To get soil moisture at different depth, this method always requires precise and vertically dense soil profile measurement or simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The produced image in this method shows measured temperature. In this method, the tumor is detected as points with higher temperature due to its characteristics [9][10][11][12][13].…”
Section: Passive Microwave Imagingmentioning
confidence: 99%
“…This enables the extraction of further information to facilitate the detection and/or visualization of the unknown temperature distribution. The proposed method assumes that the temperature distribution can be approximated by a Mixture Model (MM) of known distributions [9], as shown in equation (2).…”
Section: Temperature Reconstructionmentioning
confidence: 99%
“…It has been shown that MWR imaging can be used to detect differences in temperature distribution in the human breast when a lesion is present [2]. This is because breast tumours have electrical properties at microwave frequencies that are significantly different from those of healthy breast tissues [3], especially at early lesion development [4].…”
Section: Introductionmentioning
confidence: 99%